2017
DOI: 10.3390/en10091299
|View full text |Cite
|
Sign up to set email alerts
|

Research on an Integrated Hydrostatic-Driven Electric Generator with Controllable Load for Renewable Energy Applications

Abstract: Abstract:A hydrostatic transmission is a promising technology in renewable energy harvesting, such as wind energy and wave energy, where the hydrostatic-driven electric generator is a key energy conversion component. By using analytical and experimental methods, this paper investigates the performance of a novel hydrostatic-driven electric generator which integrates the functions of an axial piston hydrostatic motor and a permanent magnet electric generator together. The experimental platform consists of a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…A permanent magnet generator (PMG) is a type of electrical generator that uses permanent magnets to generate electricity. Unlike conventional generators that use electromagnets to generate a magnetic field, permanent magnet generators use permanent magnets as the source of the magnetic field [1,6,7].…”
Section: Permanent Magnet Generator and The Development Of Wind Energ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A permanent magnet generator (PMG) is a type of electrical generator that uses permanent magnets to generate electricity. Unlike conventional generators that use electromagnets to generate a magnetic field, permanent magnet generators use permanent magnets as the source of the magnetic field [1,6,7].…”
Section: Permanent Magnet Generator and The Development Of Wind Energ...mentioning
confidence: 99%
“…The basic principle of operation of a permanent magnet generator is the principle of electromagnetic induction. When an electric wire crosses magnetic field lines, an electromotive force (EMF) is created in the wire, which leads to the generation of an electric current [6].…”
Section: Permanent Magnet Generator and The Development Of Wind Energ...mentioning
confidence: 99%
“…From Equations (4) and 7, the average conduction loss of three-phase half-bridge inverter in one current period can be calculated as:…”
Section: Nonlinear Loss Model Of Three-phase Invertermentioning
confidence: 99%
“…As the motor drive system is the main power source of EVs, the efficiency of the drive system will directly influence their mileage endurance. Compared with induction motors (IMs) and switched reluctance motors (SRMs) [4,5], permanent magnet synchronous motors (PMSMs) with their advantage of high power density and high efficiency, can decrease the energy consumption and improve the operational mileage of EVs [6][7][8], therefore, the PMSM direct drive system has been widely applied in EVs for transportation.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [29,30] reported the feasibility of harvesting the kinetic energy in turbulent air and rainwater flow by using Tesla disk turbines with different diameters. However, the structure where the fluid turbine and the electrical generator are connected in parallel along the shaft usually results in relatively large volumes and low power density [31,32]. In addition, the aforementioned Tesla disk turbines are driven by fluid flow in pipes where the working fluid is injected nearly tangentially to rotating disks through certain nozzles.…”
Section: Introductionmentioning
confidence: 99%